Fervor and resistance in building the field of social technology in Brazil: the complex history of public policies in the two last decades - Addor, Felipe; Ingrid Michele do Nascimento, Andreia; Belo Paiva, Arquimedes (Organizações & Sociedade, 2025)
The aim of this work is to understand how social technology has developed from the programs, projects and plans of the Brazilian federal government over the last two decades (2003-2023) in interaction with its central actors, especially those located in universities and in social movements. In a markedly exploratory and qualitative approach, the Multiannual Plans (PPA), the National Science, Technology and Innovation Strategies (ENCTI), the Science, Technology and Innovation Action Plans (PACTI) and the Public Calls developed by federal institutions such as the Ministry of Science, Technology and Innovation (MCTI), the National Council for Scientific and Technological Development (CNPq) and the Financier of Studies and Projects (FINEP) were analyzed. A periodization was constructed consisting of three phases (the Great Cycle, the Descent and the Resumption) of public policies to promote Social Technology that span the last seven (7) federal governments. Finally, we sought to assess the particularities and reciprocal links built up by the web of public policies in the field of social technology, as well as the possibilities for reconfiguring the area based on the reorganization around a renewed agenda for Social Technology in Brazil.